Electronic Clearance System with SMS Notification in the Case of Guimaras State University - Mary Llourane Faith Jornadal; Julie Ann S. Panimoto; Dyadhemme Pherl J. Patiño; Vic Christopher P. Cajilig; RD V. Fortunado; Adreal Y. Pelaez; Adrian J. Forca (Program Studi Ilmu Komputer, Universitas Pakuan, 2025)
In response to the inefficiencies of manual clearance processes at Guimaras State University (GSU), this study presents the development of an Electronic Clearance System integrated with SMS Notification. Literature findings motivated researchers to craft the objective of streamlining clearance procedures and enhance accessibility for both students and employees. The system aims to reduce processing time, eliminate paperwork, and provide real-time updates to stakeholders. The methodology involved the adoption of the System Development Life Cycle (SDLC), encompassing requirements gathering, analysis, design, implementation, and testing phases. Through interviews with administrative offices at GSU, user requirements and clearance process intricacies were identified. Leveraging technologies such as PHP, MySQL, and CSS, a user-friendly web-based system was developed to facilitate clearance management. Key results of the study include a significant reduction in clearance processing time and improved user experience. By automating processes and integrating SMS notifications, the system ensures timely updates and enhances communication between stakeholders. Overall, the Electronic Clearance System with SMS Notification offers a scalable and efficient solution to streamline clearance management at GSU.